Management of refractory Pseudomonas aeruginosa infection in cystic fibrosis - Roger Sordé; Albert Pahissa; Jordi Rello (2011)
Abstract: Cystic fibrosis (CF) is the most common life-limiting inherited disease in Caucasian populations. The main cause of death in CF patients is respiratory failure resulting from chronic pulmonary infection. Pseudomonas aeruginosa is the most prevalent organism in the airway colonization of CF patients, and its persistence in the airways has been related to greater morbidity with a more rapid deterioration in lung function. P. aeruginosa has enormous genetic and metabolic flexibility that allows it to adapt and persist within the airways of CF patients, and it has the ability to easily acquire antimicrobial resistance. For these reasons, the management of infections and chronic colonization by P. aeruginosa remains a challenge for physicians. This article reviews the current and future antibacterial chemotherapy options for respiratory pseudomonal infection in CF patients. Keywords: cystic fibrosis, Pseudomonas aeruginosa , respiratory infection, antimicrobial treatment